2006
DOI: 10.1113/jphysiol.2005.104521
|View full text |Cite
|
Sign up to set email alerts
|

Limited oxygen diffusion accelerates fatigue development in mouse skeletal muscle

Abstract: Isolated whole skeletal muscles fatigue more rapidly than isolated single muscle fibres. We have now employed this difference to study mechanisms of skeletal muscle fatigue. Isolated whole soleus and extensor digitorum longus (EDL) muscles were fatigued by repeated tetanic stimulation while measuring force production. Neither application of 10 mM lactic acid nor increasing the [K + ] of the bath solution from 5 to 10 mM had any significant effect on the rate of force decline during fatigue induced by repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 54 publications
7
63
1
Order By: Relevance
“…Collectively, these results indicate that survivability of muscle tissue depends strongly on the maintenance of resting blood flow. Indeed, under such in vitro conditions, whole muscle tissue may be more damaged than single-muscle fibers (57). In contrast, in the present investigation, there were no significant changes in resting muscle [Ca 2ϩ ] i under the circulation-intact in vivo conditions.…”
Section: In Vitro Vs In Vivocontrasting
confidence: 54%
“…Collectively, these results indicate that survivability of muscle tissue depends strongly on the maintenance of resting blood flow. Indeed, under such in vitro conditions, whole muscle tissue may be more damaged than single-muscle fibers (57). In contrast, in the present investigation, there were no significant changes in resting muscle [Ca 2ϩ ] i under the circulation-intact in vivo conditions.…”
Section: In Vitro Vs In Vivocontrasting
confidence: 54%
“…It has been reported that blockade of mitochondrial respiration in skeletal muscle resulted in decreased tetanic force generation (25,26), and in patients with mitochondrial depletion syndrome, muscle weakness is one leading clinical feature (26,27). Thus, the low specific force in hypertrophic muscle due to lack of myostatin, may be attributable to the associated mitochondrial depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these issues makes analysis of mechanisms of fatigue in isolated whole muscles problematic. The relative contribution of extracellular accumulation of K ϩ or lactic acid or hypoxia was recently studied in isolated mouse muscle fatigued by repeated tetani, and under these experimental conditions, hypoxia was the most important factor (493).…”
Section: A Models Of Fatigue and Their Limitationmentioning
confidence: 99%